1980
DOI: 10.3146/i0095-3679-7-2-13
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gypsum on Yield, Grade and Incidence of Pod Rot in Five Peanut Cultivars1

Abstract: Five cultivars of peanuts, (Aruchis hypogueu L.), Florunner,Tihn, Florigiant, Ga. 194 Va. and Early Bunch, were grown at Tifion, Ga. on a Stilson loamy sand, low in calcium (356 kg/ha), and at Plains, Ga. on a Greenville sandy loam, relatively higher in calcium (752 kg/ha), for three years (1977-79) to study the response of yield, grade and incidence of pod rot with applications of gypsum. Plots were topdressed with 0, 560, 1120, or 1680 kg/ha of gypsum. Pod rot did not occur at Plains and no significant diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 7 publications
1
18
0
Order By: Relevance
“…However, in 1999, byproduct Ca at 2240 kg/ha or agricultural Ca at 1680 and 2240 kg/ha applied at plant increased peanut yield up to 22% over the non-treated control. On coarse textured soils low in residual Ca, peanut yields have been increased with Ca applications (Sullivan et al, 1974;Walker and Csinos, 1980). Jordan et al (2000) reported supplemental Ca increased pod yield of virginia-and runner-type peanut over the non-treated control at two of the five locations in the Virginia-Carolina region.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…However, in 1999, byproduct Ca at 2240 kg/ha or agricultural Ca at 1680 and 2240 kg/ha applied at plant increased peanut yield up to 22% over the non-treated control. On coarse textured soils low in residual Ca, peanut yields have been increased with Ca applications (Sullivan et al, 1974;Walker and Csinos, 1980). Jordan et al (2000) reported supplemental Ca increased pod yield of virginia-and runner-type peanut over the non-treated control at two of the five locations in the Virginia-Carolina region.…”
Section: Resultsmentioning
confidence: 96%
“…Garren (1964) first reported that high rates of Ca resulted in a reduction in diseased or rotted peanut pods. Walker and Csinos (1980) stated that under severe disease pressure with several cultivars, disease decreased for all cultivars as the rate of Ca increased. At the Atascosa Co. location in 1998, no differences in disease incidence were noted between the non-treated control and any Ca treatment (Table 2).…”
Section: Methodsmentioning
confidence: 98%
“…Lack of sufficient Ca in the fruiting zone causes numerous empty pods, "pops" or seed with damaged embryos, "dark plumules" (13). High seed Ca may also increase germina-tion (6) and decrease the incidence of pod rot (14). Inadequate B during seed development often causes depressed internal cotyledonary cavities, "hollow heart" (13).…”
mentioning
confidence: 99%
“…The use of gypsum reduced the incidence of groundnut pod rot and increased the pod yield (Walker and Csinos, 1980;Chen and Huang, 1992;Ismail and Abd-El-Momen, 2007). Humic substances have been proven to improve the soil fertility and increase the availability of nutrients and consequently increase plant growth and yield (Moraditochaee, 2012).…”
Section: Introductionmentioning
confidence: 99%